ANALISIS PENYISIHAN PIUTANG TAK TERTAGIH PADA CV. MITRA SERVICE - Ulum, Khoirul; Azizah, Ayu (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
This research was conducted with the aim of analyzing the reserve for bad debts loss at the company CV. Service Partners for the balance sheet reporting period as of September 30, 2022. From the results of the research that the authors did for 5 months and on the basis of the data of the Balance Sheet report as of December 31, 2021 and the Balance Sheet report as of September 30, 2022, CV. Service Partners have not made a provision for uncollected receivables. In this study, the author uses the age of receivables analysis to calculate and estimate the allowance for losses on receivables on the basis of the detailed list of accounts receivable data as of September 30, 2022. Furthermore, from the details of the receivables, an analysis of the age of receivables is compiled, namely the age group of accounts receivable 0-30 days, 31- 60 days, and >60 days with allowance for accounts receivable rates of 10%, 15% and 15% (table-3 & table-4). From the results of multiplying the receivables allowance rate and the amount of receivables that have been grouped based on the age of the receivables, an allowance for losses on bad debts is Rp. 75,641,783,- (table-5) and the effect on the current year’s profit and loss forecast decreased to Rp. 397.201.853,-.